Realismo da interpretação. A legitimidade da representação em Fernando Gil - Sousa, Inês (Trabalhos de Antropologia e Etnologia, 2020)
The realism of interpretation is a Fernando Gil’s idea developed in Mimésis e Negação, which deals with the epistemic nature of knowledge. The main aim of this paper is to demonstrate that the realism of interpretation corroborates the representativeness of representation. The paper is composed of three moments, whose goals are as follows: 1) to characterize the nature and the epistemological status of representation according to the realism of interpretation’s main postulations; 2) to highlight an inter-relationship between both the sensible and the intelligible representation, that is grounded on a shared designative nature; 3) to discuss how can the content of representation – which is determined by perceptual experience – point towards a transcendental “principle of affinity”.